Reimagining Theory of Planned Behaviour in Exploitation of Public Private Partnership Opportunities to SMEs (Global Journal of Management and Business Research, 2022)
In light of the rapid increase SMEs importance to economy this study aims to contribute to the existing literature regarding exploitation of opportunities by applying the Theory of Planned Behaviour TPB model to predict exploitation of opportunities favouring SMEs The TPB is particularly suitable for this type of study since it has been suggested to be an effective model in predicting how and why some people intend to exploit business opportunities whereas others do not Garba et al 2014 Crispeels et al 2012 de Jong 2013 Nangoli et al 2013 More generally speaking the TPB seems to be an effective predictive model in fields that lead to a certain degree of behavioural change from individuals